The validity and reliability of the force plates and the linear position transducer in measuring countermovement depth and velocity during countermovement jump - Li, Z.; Ma, W.; Zhang, L.; Zhu, W.; Xie, Q.; Sun, Y. (Sensors, 2025)
Countermovement jump (CMJ) is a key test for evaluating lower-limb neuromuscular function, and accurate measurement of countermovement depth (CMD) and countermovement velocity (CMV) is critical for determining optimal performance. However, the measurement validity and reliability of CMD and CMV—particularly when obtained from force plates (FP) and linear position transducers (LPT)—have remained uncertain. This study determined the validity and reliability of FP and LPT for measuring CMD and CMV. Twenty-eight male recreational athletes performed the CMJ test, and the variables were synchronously acquired by Motion Capture (MC), FP, and LPT. The test was divided into two sessions, with participants completing three maximal effort CMJs per session, and the second session occurred more than 48 h after the first. The reliability was evaluated using the intraclass correlation coefficient (ICC), and the validity was evaluated with linear Pearson`s correlation coefficient (r), one-way ANOVA with repeated measures, and Bland-Altman plots. The reliability results for FP and LPT indicated good to excellent (ICC = 0.809-0.900). Compared with MC, the FP showed a high to very high correlation (r = 0.894-0.937), and the LPT showed a high correlation (r = 0.721-0.726). When precise quantification of CMD/CMV is required, FP should be preferred. If only an LPT is available, it is best used for within-athlete longitudinal monitoring with a consistent setup, and cross-device comparisons should be avoided.